Differential gene expression analysis of 'Chili' (Pyrus bretschneideri) fruit pericarp with two types of bagging treatments. (8th March 2017) - Wang, Yuling; Zhang, Xinfu; Wang, Ran; Bai, Yingxin; Liu, Chenglian; Yuan, Yongbing; Yang, Yingjie; Yang, Shaolan
Abstract: Preharvest bagging is a simple, grower-friendly and safe physical protection technique commonly applied to many fruits, and the application of different fruit bags can have various effects. To explore the molecular mechanisms underlying the fruit quality effects of different bagging treatments, digital gene expression (DGE) profiling of bagged and unbagged 'Chili' ( Pyrus bretschneideri Rehd.) pear pericarp during development was performed. Relative to unbagged fruit, a total of 3022 and 769 differentially expressed genes (DEGs) were detected in the polyethylene (PE)-bagged and non-woven fabric-bagged fruit, respectively. DEGs annotated as photosynthesis-antenna proteins and photosynthesis metabolism pathway were upregulated in non-woven fabric-bagged fruit but downregulated in the PE-bagged fruit. Non-woven fabric bagging inhibited lignin synthesis in 'Chili' pear pericarp by downregulating DEGs involved in phenylpropanoid biosynthesis; consequently, the fruit lenticels in non-woven fabric-bagged fruit were smaller than those in the other treatments. The results indicate that the non-woven fabric bagging method has a positive effect on the appearance of 'Chili' pear fruit but neither of the two bagging treatments is conducive to the accumulation of soluble sugar. Abstract : Crop cultivation: Bagging for fruit quality Researchers have evaluated the effect of preharvest bagging on gene expression in pear fruit. Shaolan Yang and colleagues from China's Qingdao Agricultural University sequenced RNA from bagged and unbagged fruit on 15-year old trees of the 'Chili' cultivar. They found that bagging with polyethylene affected the expression of roughly 3, 000 genes, while using non-woven fabric bags changed the expression of nearly 800 genes. Genes related to photosynthesis were less active in the polyethylene bags but increased their activity in fabric bags. Fabric bags also led to an increase in lignin synthesis genes, resulting in smoother, brighter fruit with smaller corky brown spots known as lenticels. Both types of bag led to lower sugar levels than in unbagged fruit. Nevertheless, the researchers recommend the use of fabric bags to improve the appearance of fruit of this variety.